Racial/Ethnic Disparities in Measures of Self-reported Psychosocial States and Traits during Pregnancy - Grobman, William A.; Parker, Corette; Wadhwa, Pathik D.; Willinger, Marian; Simhan, Hyagriv; Silver, Bob; Wapner, Ron J.; Parry, Samuel; Mercer, Brian; Haas, David; Peaceman, Alan M.; Hunter, Shannon; Wing, Deborah; Caritis, Steve; Esplin, Sean; Hoffman, Matt; Ludmir, Jack; Iams, Jay; Long, Emily; Saade, George; Reddy, Uma M.; for the National Institute of Child Health Human Development nuMoM2b Network, Bethesda, MD (American Journal of Perinatology, 2016)
Background The aim of this study was to determine whether racial/ethnic differences in psychosocial measures, independent of economic status, exist among a large population of pregnant nulliparas.Methods Between October 2010 and September 2013, nulliparous women at eight U.S. medical centers were followed longitudinally during pregnancy and completed validated instruments to quantify several psychosocial domains: Cohen Perceived Stress Scale, trait subscale of the Spielberger Anxiety Inventory, Connor–Davidson Resilience Scale, Multidimensional Scale of Perceived Social Support, Krieger Racism Scale, Edinburgh Postnatal Depression Scale, and the Pregnancy Experience Scale. Scores were stratified and compared by self-reported race, ethnicity, and income.Results Complete data were available for 8,128 of the 10,038 women enrolled in the study. For all measures, race and ethnicity were significantly associated (p < 0.001) with survey scores. Non-Hispanic black (NHB) women were most likely to score in the most unfavorable category for all measures, with the exception of the Pregnancy Experience Scale. The magnitude of these differences did not differ by income status (interaction, p > 0.05) except on the Krieger racism survey and the Edinburgh depression survey, which were exacerbated among NHB women with higher income (interaction, p < 0.001).Conclusion Significant racial/ethnic disparities, independent of income status, exist in psychosocial measures during pregnancy.
Keywords: psychosocial; stress; disparities; pregnancy